PENGEMBANGAN SISTEM EKSPERIMEN VISKOSITAS BERBASIS PERSONAL KOMPUTER DAN MIKROKONTROLER MCS-51 - Yohandri, Yohandri (IAIN Batusangkar, 2010)
In this work, viscosity experiment system based on personal computer and microcontroller MCS-51 has been developed. The new model of viscosity experiment system is purposed to perfom the time and viscosity calculation automatically on the personal computer. The graph and statical analysis are used to determine characteristics of LDR sensor and experiment system such as sensitivity, accuracy, and precision. There were four main results of this research as follow : 1). LDR sensor resistance decreased with increasing light intensity and sensitivity of sensor was -11,55.(I)-1,56, 2). The comparator output voltage are two condition depend on light intensity, below 400 lux the output voltage is 4.54 Volt and for above is 0.59 Volt, 3). The accuracy and precision average of system timer was high, each of it was 99.9% and 0.97, 4). Ability of system to determine the value of the liquids viscosity has been tested and obtained three results for glycerin, SAE40 Oil, and cooking oil which the value of each sequence are 1121.99 mPas, 795.08 mPas and 79.78 mPas. Based on repeated measurement in viscosity, the precision of system have been obtained which average 0.994. Key words: viscosity, personal computer, microcontroller, sensitivity, accuracy, precesion